Differential Influence of Blogs Across Different Stages of Decision Making: The Case of Venture Capitalists1 - Aggarwal, Rohit; Singh, Harpreet (MIS Quarterly, 2013)
In this paper, we study the differential influence of online user-generated content (UGC), specifically blogs, across the multiple stages of decision making of venture capitalists: screening stage, choice stage, and contract stage. We conjecture that, first, blogs are influential at the screening stage; second, after the screening stage, blogs are noninfluential since decision makers evaluate entities closely at later stages; third, blogs increase the interest from multiple decision makers which in turn increases the cost of the deal for a decision maker. This empirical investigation provides support for the hypotheses, which we tested for funding decisions by venture capitalists in information technology ventures. In particular, this study indicates that blogs can help managers in getting their products/services selected at the screening stage, but, beyond that, blogs do not help directly. However, since more decision makers screen products/services that receive blog coverage, the competition among decision makers helps managers in negotiating better contract terms. We advance the boundary of existing studies on the influence of UGC from single stage process to multiple stages.